Initial evidence for the criterion-related and structural validity of the long versions of the Coach-Athlete Relationship Questionnaire - Rhind, D. J. A.; Jowett, S. (European Journal of Sport Science, 2010)
The aim of the present study was to develop and initially validate a longer version of the direct (Jowett & Ntoumanis, 2004) and meta-perspectives (Jowett, 2009a, 2009b) of the Coach-Athlete Relationship Questionnaire (CART-Q). In Study 1, instruments (e.g. questionnaires, scales, and inventories) that have been used to assess relationship quality in the broader psychological literature were examined and items potentially relevant to the coach-athlete relationship were identified. The content validity of the identified items was then assessed using expert panels. A final questionnaire was subsequently prepared and administered to 693 participants (310 coaches and 383 athletes). Confirmatory factor analysis was employed to assess the multidimensional nature of the questionnaire based on the 3Cs (i.e. closeness, commitment, and complementarity) model of the coach-athlete relationship. The findings indicated that the direct and meta-perspective items of the long versions of the CART-Q approached an adequate data fit. Moreover, evidence for the internal consistency and criterion validity of the new instruments was also obtained. In Study 2, the newly developed measure was administered to an independent sample of 251 individuals (145 athletes and 106 coaches). Further statistical support was gained for the factorial validity and reliability of the longer version of the CART-Q.